OPTIMAL ENERGY REGULATION PERFORMANCE OF DELAY-TIME SYSTEMS - T. BAKHTIAR (MILANG Journal of Mathematics and Its Applications, 2007)
This paper studies the regulation performance limi- tation of delay-time systems. The performance is measured by the energy of the control input with respect to an impulse dis- turbance function. We ﬁrst provide the analytical closed-form expression of the optimal performance for minimum phase case by reviewing the existing result. We then extend the problem to non-minimum phase case by exploiting the results of linear time- invariant discrete-time and delta domain cases.